Hubungan Kerapatan Padang Lamun Dengan Kelimpahan Makrozoobentos Di Pulau Pramuka - Putri, Vanya Amelia; Cahyadi, Ferry Dwi; Prasetiyo, Himawan (Journal of Tropical Marine Science, 2024)
Pramuka Island is one of the islands in the Seribu Islands which has a number of marine ecosystems such as seagrass and macrozoobenthos. The aim of this research is to determine the relationship between seagrass density and macrozoobenthos abundance. This research was carried out by applying the purposive sampling method to determine research locations at 3 stations and 3 plots with 50 m transect lines and Pearson Product Moment or simple correlation analysis to determine the relationship between seagrass density and macrozoobenthos abundance. The seagrass species found on Pramuka Island form mixed vegetation with 5 seagrass species and the highest density is Thalassia hemprichii. The macrozoobenthos found included the Holothuroidea, Bivalvia and Gastropod classes with the highest abundance being the Holothuroidea class. The relationship between seagrass density and macrozoobenthos abundance shows a strong relationship with a correlation value of 0.997 and shows a positive (+) linear direction, meaning that the higher the seagrass density value, the higher the macrozoobenthos abundance.